Sense of Coherence and Health-Related Quality of Life in Patients With Brain Metastases - Qiu, Xian; Zhang, Nan; Pan, Si-Jian; Zhao, Peng; Wu, Bei-Wen (Frontiers in Psychology, 2020)
With improvements in treatments for primary tumor and brain metastases (BM), the life expectancy of patients with advanced cancers is increasing; thus, helping patients with BM maintain quality of life is becoming increasingly important. Sense of coherence (SOC) has been found to be closely related to health-related quality of life (HRQoL) in patients with chronic diseases; however, this relationship has not been validated in patients with BM. This study first examined the relationship between SOC and HRQoL in patients with BM, and further identified factors associated with SOC in these patients. Patients with BM reported lower scores for most of the functioning subscales and for the general rating of quality of life, and higher scores for most of the symptom subscales, compared with a normative sample. SOC was significantly correlated with most aspects of HRQoL in patients with BM. Further, SOC in the patients was associated with awareness of the disease, possession of religious belief, and type of primary cancer. These results validate the close relationship between SOC and HRQoL in patients with BM, and indicate that SOC is associated with awareness of illness and religious belief.